Antidiabetic Activity of Zingiber officinale Roscoe Rhizome Extract: an In Vitro Study - Kusumarn Noipha; Putrada Ninla-Aesong (HAYATI Journal of Biosciences, 2018)
The potential roles of Zingiber officinale Roscoe (ginger) for treating and preventing diabetes have been investigated in both humans and experimental animals. However, the mode of its action has not yet been elucidated. This study aimed to investigate the effects of ginger extract on glucose uptake activity and its activation pathway in L6 myotubes. Cells were co-cultured for 24 h with a variable concentration of either ginger extract or 2 mM metformin or 200 nM insulin or 20 μM Troglitazone (TGZ), followed by a 10-min 2-[3H]-deoxy-D-glucose (2-DG) uptake. The levels of glucose transporters 1 (GLUT1) and GLUT4 protein and mRNA expression were determined. Ginger extract at 400 μg/ml significantly enhanced glucose uptake in L6 myotubes (208.03 ± 10.65% above basal value, p<0.05) after co-culture for 24 h. The ginger-enhancement of glucose uptake was inhibited by 3.5 μM cycloheximide, a protein synthesis inhibitor, 1 μM wortmannin (Phosphatidylinositol 3-Kinase (PI3 kinase) inhibitor) and 15 nM rapamycin (mammalian target of rapamycin (mTOR) inhibitor). The enhancement of glucose transport by ginger extract at 400 μg/ml was accompanied with the increased expression of GLUT1 protein (1.60 ± 0.20, 2.03 ± 0.19, and 2.25 ± 0.35 folds of basal at 4, 8, and 24 h, respectively p<0.05) and mRNA (1.22 ± 0.96, 1.45 ± 0.93, 1.91 ± 0.75, 2.32±0.92, and 2.20 ± 0.64 folds of basal at 1, 2, 4, 8, and 24 h, respectively p<0.05) in a time-dependent manner. Z. officinale Roscoe rhizome extract increase glucose transport activity of L6 myotubes by enhancing GLUT1 expression, the results of PI3-Kinase and 5’-AMP-activated kinase (AMPK) stimulation.